2010
DOI: 10.4103/0972-124x.76917
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and periodontitis

Abstract: The main aim of this review is to update the reader with practical knowledge concerning the relationship between diabetes mellitus and periodontal diseases. Exclusive data is available on the association between these two chronic diseases till date. Articles published on this relationship often provide the knowledge of definitions of diabetes mellitus and periodontal diseases, prevalence, extent, severity of periodontal disease, complications of diabetes along with the possible underlying mechanisms. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 55 publications
4
44
0
Order By: Relevance
“…With the previously described effects of CMC 2.24 as MMP and cytokine inhibitors, and with the demonstration that CMC 2.24, but not other triketonic CMCs (CMC 2.23 and CMC 2.14), can significantly inhibit alveolar (periodontal) bone loss in diabetic rats (27), it was of great interest to see how this compound performed in an animal model of endotoxin-induced periodontitis complicated by type I diabetes. Although diabetes by itself can induce periodontitis (43), we decided in this experiment to use the diabetic rat model with endotoxin-induced periodontitis to induce a more severe and aggressive form of periodontitis because of the short duration of this experimental protocol (4 wk) and because this particular combination of local and systemic disease is often seen clinically and is particularly difficult to treat effectively (25,50).…”
Section: Discussionmentioning
confidence: 99%
“…With the previously described effects of CMC 2.24 as MMP and cytokine inhibitors, and with the demonstration that CMC 2.24, but not other triketonic CMCs (CMC 2.23 and CMC 2.14), can significantly inhibit alveolar (periodontal) bone loss in diabetic rats (27), it was of great interest to see how this compound performed in an animal model of endotoxin-induced periodontitis complicated by type I diabetes. Although diabetes by itself can induce periodontitis (43), we decided in this experiment to use the diabetic rat model with endotoxin-induced periodontitis to induce a more severe and aggressive form of periodontitis because of the short duration of this experimental protocol (4 wk) and because this particular combination of local and systemic disease is often seen clinically and is particularly difficult to treat effectively (25,50).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between DM and periodontal disease has been studied extensively for >50 years. It has been suggested that a reciprocal relationship exists between type 2 DM (T2DM) and periodontitis 6,7 . A case‐control study showed that patients with T2DM are more susceptible to developing severe periodontal disease, 8 a conclusion that has been reinforced by the results of a meta‐analysis, which demonstrated that the overall differences in average probing depths (PDs) and clinical attachment loss (AL) were significantly greater in patients with DM compared with patients without DM 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Among these, we can list generalized diseases, such as rheumatoid arthritis (Zheng et al 2015), cardiovascular disease (Ordovas and Mooser 2006), and pulmonary diseases (Scannapieco and Genco 1999), as well as brain and liver abscesses (Wagner et al 2006). Other such illnesses include gastrointestinal cancer (Meurman and Grönroos 2010), breast cancer (Laidi et al 2016), cirrhosis (Bajaj et al 2015), and diabetes (Maruyama et al 2007;Deshpande et al 2010;Farag and Gaballa 2011). More recently, links with pregnancy (Digiulio et al 2015), the human immunodeficiency virus (HIV) (Kistler et al 2015), and acquired immune deficiency syndrome (AIDS) have also been described (Zheng et al 2015).…”
Section: The Huat Microbiota and General Disordersmentioning
confidence: 99%